2022
DOI: 10.1096/fj.202200145r
|View full text |Cite
|
Sign up to set email alerts
|

Tafazzin deficiency in mouse mesenchymal stem cells promote reprogramming of activated B lymphocytes toward immunosuppressive phenotypes

Abstract: Barth Syndrome (BTHS) is a rare X‐linked genetic disorder caused by mutation in the TAFAZZIN gene. Tafazzin (Taz) deficiency in BTHS patients results in an increased risk of infections. Mesenchymal stem cells (MSCs) are well known for their immune‐inhibitory function. We examined how Taz‐deficiency in murine MSCs impact their ability to modulate the function of lipopolysaccharide (LPS)‐activated wild type (WT) B lymphocytes. MSCs from tafazzin knockdown (TazKD) mice exhibited a reduction in mitochondrial cardi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…Increased PI3K expression and activity is associated with enhancement of immunosuppression by MSCs 7 . We previously demonstrated that PI3K protein expression was elevated in MSCs isolated from TazKD mice 5 . MSCs were isolated from bone marrow of WT and TazKD mice and PI3K mRNA expression determined.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Increased PI3K expression and activity is associated with enhancement of immunosuppression by MSCs 7 . We previously demonstrated that PI3K protein expression was elevated in MSCs isolated from TazKD mice 5 . MSCs were isolated from bone marrow of WT and TazKD mice and PI3K mRNA expression determined.…”
Section: Resultsmentioning
confidence: 96%
“…Splenic naïve B lymphocytes from WT and TazKD mice were isolated and cultured as previously described 6 . For co-culture studies with WT or TazKD MSCs, naïve or TazKD B cells were first stimulated by incubation with LPS (10 μg/ml) for 24 h and were then co-cultured with MSCs for 24 h in 24-well plates at a ratio of 1:10 (MSCs:B cells) as previously descibed 5 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations